Analisis Perwilayahan Komoditas dan Kontribusi Kopi Arabika Terhadap Pembangunan Wilayah Kabupaten Tapanuli Utara - Rita Herawaty Bangun (Jurnal Agriuma, 2020)
Arabica coffee is one of the plantation commodities that has an important role in the economy and regional development in North Tapanuli Regency. This study aims to identify the area of production base of Arabica coffee commodity, its distribution characteristics and the role of the Arabica coffee commodity in supporting regional development in North Tapanuli Regency. The data used are secondary data from 2016-2018. Data analysis methods used are location quotient analysis, localization and specialization analysis, basic service ratio analysis and area multiplier. The results showed that the Arabica coffee base area based on production indicators in North Tapanuli District were Parmonangan District, Sipoholon District, Tarutung District, Siatas Barita District, Pangaribuan District, Sipahutar District, Siborongborong District, Pagaran District, and Muara District. Arabica coffee commodity farming is not localized and concentrated in a particular sub-district area but rather spreads in several sub-districts and does not specialize in Arabica coffee commodity farming. Arabica coffee commodity can support plantation activities and regional development in North Tapanuli Regency.